2020
DOI: 10.1101/2020.05.12.090407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiological correlates of visual backward masking in patients with bipolar disorder

Abstract: Background:In visual backward masking (VBM), a target is followed by a mask that decreases target discriminability. Schizophrenia patients (SZ) show strong and reproducible masking impairments, which are associated with reduced EEG amplitudes. Patients with bipolar disorder (BP) show masking deficits, too. Here, we investigated the neural EEG correlates of VBM in BP.Methods: 122 SZ, 94 unaffected controls, and 38 BP joined a standard VBM experiment. 123 SZ, 94 unaffected controls and 16 BP joined a correspondi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Resting microstate dynamics data of 27 patients and 27 controls have already been published in previous work 6 . Masking and ERP data of 89 patients, 39 siblings, and 63 controls have already been published [47][48][49] . Patients with schizophrenia and their siblings were recruited from the Tbilisi Mental Health Hospital or the psycho-social rehabilitation center.…”
Section: Methodsmentioning
confidence: 99%
“…Resting microstate dynamics data of 27 patients and 27 controls have already been published in previous work 6 . Masking and ERP data of 89 patients, 39 siblings, and 63 controls have already been published [47][48][49] . Patients with schizophrenia and their siblings were recruited from the Tbilisi Mental Health Hospital or the psycho-social rehabilitation center.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study indicated that visual backward masking deficiency is not unique to schizophrenia, but a larger range of functional psychosis. Both SCH and BD may suffer insufficient objective strengthening (18). A recent study showed that particular neurological functions can distinguish SCH from BD and also indicate a presumptive endogenous phenotype that can distinguish the genetic susceptibility of SCH from another severe psychological disease (19).…”
Section: Introductionmentioning
confidence: 99%
“…All participants took part in a battery of tests comprising perceptual and cognitive tasks as well as EEG recordings. Data of 101 patients and 75 controls have already been published in different contexts 13,[41][42][43] , while data of the other 20 participants have not been published yet. Patients were recruited from the Tbilisi Mental Health Hospital or the psycho-social rehabilitation center.…”
Section: Methods Participantsmentioning
confidence: 99%
“…wrote the paper. Data of 101 patients and 75 controls have already been published in different contexts 13,4850 . The code that support the findings of this study are available upon request.…”
Section: Acknowledgementsmentioning
confidence: 99%